Faktor Yang Mempengaruhi Keputusan Konsumen Menggunakan Kartu Kredit di Mall Semarang - Calvin Suryo Wibowo; Sentot Suciarto Athanasius (JEMAP, 2019)
This research aimed to know and analyze what factors affect the decision in using credit card and to know which factor was the most dominant in purchase decision using credit card of Paragon City Mall consumers in Semarang City. Research method conducted was quantative research, which variables measured by questionnaires by Likert scale. Data collection was conducted with list of questions or questionnaires. Data processing used SPSS software version 19, with factor analysis. Research result showed that 5 factors which influenced purchase decision using credit card mall consumers, namely transaction and promotion factor, credit card advantage factor, extra factor, having credit card factor, and prestige factor. The dominant factor among five factors was transaction and promotion factor which consisted variables easing transaction, discount in transaction, buy one get one, and point from transaction.